Enlargement of the WHO international repository for platelet transfusion‐relevant bacteria reference strains. Issue 8 (27th September 2017) - Spindler‐Raffel, E.; Benjamin, R. J.; McDonald, C. P.; Ramirez‐Arcos, S.; Aplin, K.; Bekeredjian‐Ding, I.; de Korte, D.; Gabriel, C.; Gathof, B.; Hanschmann, K.‐M.; Hourfar, K.; Ingram, C.; et al.
Abstract : Background and Objectives: Interventions to prevent and detect bacterial contamination of platelet concentrates (PCs) have reduced, but not eliminated the sepsis risk. Standardized bacterial strains are needed to validate detection and pathogen reduction technologies in PCs. Following the establishment of the First International Reference Repository of Platelet Transfusion‐Relevant Bacterial Reference Strains (the 'repository'), the World Health Organization (WHO) Expert Committee on Biological Standardisation (ECBS) endorsed further repository expansion. Materials and Methods: Sixteen bacterial strains, including the four repository strains, were distributed from the Paul‐Ehrlich‐Institut (PEI) to 14 laboratories in 10 countries for enumeration, identification and growth measurement on days 2, 4 and 7 after low spiking levels [10–25 colony‐forming units (CFU)/PC bag]. Spore‐forming ( Bacillus cereus PEI‐B‐P‐07‐S, Bacillus thuringiensis PEI‐B‐P‐57‐S), Gram‐negative ( Enterobacter cloacae PEI‐B‐P‐43, Morganella morganii PEI‐B‐P‐74, PEI‐B‐P‐91, Proteus mirabilis PEI‐B‐P‐55, Pseudomonas fluorescens PEI‐B‐P‐77, Salmonella choleraesuis PEI‐B‐P‐78, Serratia marcescens PEI‐B‐P‐56) and Gram‐positive ( Staphylococcus aureus PEI‐B‐P‐63, Streptococcus dysgalactiae PEI‐B‐P‐71, Streptococcus bovis PEI‐B‐P‐61) strains were evaluated. Results: Bacterial viability was conserved after transport to the participating laboratories with one exception ( M. morganii PEI‐B‐P‐74). All other strains showed moderate‐to‐excellent growth. Bacillus cereus, B. thuringiensis, E. coli, K. pneumoniae, P. fluorescens, S. marcescens, S. aureu s and S. dysgalactiae grew to >10 6 CFU/ml by day 2. Enterobacter cloacae, P. mirabilis, S. epidermidis, S. bovis and S. pyogenes achieved >10 6 CFU/ml at day 4. Growth of S. choleraesuis was lower and highly variable. Conclusion: The WHO ECBS approved all bacterial strains (except M. morganii PEI‐B‐P‐74 and S. choleraesuis PEI‐B‐P‐78 ) for repository enlargement. The strains were stable, suitable for spiking with low CFU numbers, and proliferation was independent of the PC donor.